The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jgm.3163
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the expression profiles and functions of circRNAs in a newborn hyperoxia‐induced rat bronchopulmonary dysplasia model

Abstract: Background: Bronchopulmonary dysplasia (BPD) is a severe chronic lung disease in preterm infants. Circular RNAs (circRNAs) are key regulators of various biological processes. The present study aimed to explore the biological roles of circRNAs in BPD pathogenesis. Methods:A newborn BPD rat model was developed to construct a circRNA library;Illumina deep sequencing (Illumina, San Diego, CA, USA) was used to reveal differential expression of circRNAs in the hyperoxia-induced BPD rat models. Sanger sequencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…CircRNAs were thought to be new star RNAs due to recent discovery of their diverse functions, vast abundance, and frequent tissue-specific expression, and played important roles in various cancers [19]. Further studies indicated that some circRNAs also played a important role in various types of non-cancer diseases and provided potential implications in accurate diagnosis and therapies [11,20]. While, only a few studies on the role of circRNAs in orthopedic disorders have been reported, and the contributions of circRNAs to pathogenesis of aseptic loosening remain basically unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs were thought to be new star RNAs due to recent discovery of their diverse functions, vast abundance, and frequent tissue-specific expression, and played important roles in various cancers [19]. Further studies indicated that some circRNAs also played a important role in various types of non-cancer diseases and provided potential implications in accurate diagnosis and therapies [11,20]. While, only a few studies on the role of circRNAs in orthopedic disorders have been reported, and the contributions of circRNAs to pathogenesis of aseptic loosening remain basically unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miRNAs can be used as biomarkers for certain diseases. In addition, our previous studies have demonstrated several novel circular RNAs, which may be associated with the pathophysiology of BPD (Cheng et al, 2020). To identify the miRNAs participated in the BPD, the expression profiles of the miRNAs were examined at 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…We used a newborn rat model of BPD; 64 newborn Sprague-Dawley (SD) rats were randomly assigned to a hyperoxia group (exposure to 85% O 2 ) from day of birth or normoxia group (exposure to 21% O 2 ) based on our previous studies (Cheng et al, 2020). Foster rats in a hyperoxic chamber were rotated daily to avoid oxygen toxicity.…”
Section: Animal Model and Tissue Specimensmentioning
confidence: 99%
“…The potential regulatory lncRNA–miRNA–mRNA and circRNA–miRNA–mRNA pathways are therefore constructed on the basis of their shared bridge miRNAs imprinted with miRNA responsive elements (MREs). Although primitive studies have illustrated the putative circRNA-mediated ceRNA network in the pathogenesis of rat BPD model ( Cheng et al, 2020 ), the comprehensive lncRNA–miRNA–mRNA and circRNA–miRNA–mRNA networks supported by physiological evidence are largely unknown. Moreover, priming and preconditioning of CB-MNCs or UC-MSCs with different cytokines or growth factors are of great importance in cell therapy-based treatment of BPD.…”
Section: Introductionmentioning
confidence: 99%